Basal functional status predicts one-year mortality after a heart failure hospitalization in elderly patients — The RICA prospective study. (1st March 2018) - Chivite, David; Formiga, Francesc; Corbella, Xavier; Conde-Martel, Alicia; Aramburu, Óscar; Carrera, Margarita; Dávila, Melitón Francisco; Pérez-Silvestre, José; Manzano, Luis; Montero-Pérez-Barquero, Manuel; ,
Abstract: Background: Dependence for basic activities of the daily living (ADL) relates to adverse outcomes in elderly acute heart failure (AHF) patients. Methods: We evaluated patients ≥ 75 years admitted because of AHF, divided according to preadmission Barthel Index (BI) category: severe (BI 0–60), moderate (BI 61–90) and slight dependence or independence for basic ADL (BI 91–100). We compared their baseline characteristics and used logistic regression models to determine whether a BI ≤ 60 confers higher one-year mortality risk. Results: We included 2195 patients, mean age 83 years; 57% women, Charlson Index 3, 65% with preserved left ventricular ejection fraction. Their median preadmission BI was 90 (65–100); 21.7% had BI ≤ 60. Patients with BI ≤ 60 were older, more often females, with higher comorbid and cognitive burden and more likely to be institutionalized. 560 patients (26%) died within the follow-up period. A preadmission BI ≤ 60 was significantly associated with higher risk of 12-month mortality (HR 1.42, 95% CI 1.14–1.77) together with male sex (1.27, 1.04–1.54), valve disease (1.49, 1.20–1.83), worse preadmission NYHA class (1.44, 1.20–1.73), stage IV chronic kidney disease (1.70, 1.35–2.15), pulmonary edema (1.33, 1.01–1.76), no family support (1.47, 1.06–2.06), and higher Charlson Comorbidity Index (1.09, CI 1.05–1.13) and Pfeiffer cognitive screening questionnaire scores (1.10, 1.05–1.14). Conclusion: Among elderly AHF patients, the presence of severe (BI ≤ 60) preadmission dependence for basic ADL confers a significant and independent risk of one-year post-discharge mortality.